2022
DOI: 10.46747/cfp.6803e87
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of concussion symptoms in the context of premature return to learn and return to play

Abstract: Objective To determine whether the proportion of sport-related concussion (SRC) cases among student athletes that resulted in a relapse of their symptoms due to premature return to play (RTP) or premature return to learn (RTL) has changed compared with a prior (2006 to 2011) study.Design Retrospective cohort study of electronic medical record charts from a 5-year period (2011 to 2016) compared with previous data.Setting A sport and exercise medicine physician's office-based practice in Ontario.Participants Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…3 This can result in exposure to another head injury before recovery is complete, resulting in prolonged recovery. 4,5 An objective diagnostic aid has the potential to improve concussion recognition and reduce or prevent disability associated with premature RTP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 This can result in exposure to another head injury before recovery is complete, resulting in prolonged recovery. 4,5 An objective diagnostic aid has the potential to improve concussion recognition and reduce or prevent disability associated with premature RTP.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current symptom-based method of concussion diagnosis has been criticized for being subjective, allowing injured athletes to downplay symptoms to avoid being removed from play . This can result in exposure to another head injury before recovery is complete, resulting in prolonged recovery . An objective diagnostic aid has the potential to improve concussion recognition and reduce or prevent disability associated with premature RTP.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study examines relapse and explores why rates are higher with return to learning than return to play (page e87). 2 Qualitative research focuses on challenges teenage girls face in returning to school after concussion, revealing important findings about the unique social pressures they endure (page 203). 3 Psychiatrist Dr Julia Gibson has created thought-provoking artwork to complement the article.…”
Section: What If This Happens Again? What If This Never Ends?mentioning
confidence: 99%
“…6 Furthermore, a five-year, retrospective study by Carson et al found that 43.5% of SRCs returned to play too soon. 7 SRCs are challenging to manage due to the underlying pathophysiology. A rapid change in intracranial velocity results in axonal shearing and cerebral edema creating metabolic changes and reduced cerebral blood flow.…”
Section: Background and Introductionmentioning
confidence: 99%
“…Although prolonged and complete cognitive rest has been shown to delay recovery, 17 Carson et al found that 44.7% of athletes with SRCs returned to full academic participation too soon, and findings from the Ivy League-Big Ten Epidemiology Study show that athletes who return to full academics too soon take longer to recover from SRC and that improved clarity in the timing of RTL is warranted. 7,18 Authors have suggested that impairments in working memory and attentional control can also lead to impairments in lower extremity motor control. 19 However, these domains can be improved with targeted interventions, including physical therapy.…”
Section: Background and Introductionmentioning
confidence: 99%